Embedded Design and Implementation of Mobile Robot for Surveillance Applications - Abdulkareem Sh. Mahdi Al-Obaidi; Arif Al-Qassar; Ahmed R. Nasser; Ahmed Alkhayyat; Amjad J. Humaidi; Ibraheem K. Ibraheem (Universitas Pendidikan Indonesia, 2021)
The surveillance and security of areas such as home, laboratory, office, factory, and airports, are important to prevent any threatening to human lives. Mobile robots are proven their effectiveness in a large number of applications, especially in hazardous areas where they can be remotely controlled by humans to accomplish certain tasks. This research paper presents a design and implementation of a mobile robot for surveillance and security applications. The main objective of the design is to lower the cost and the power consumption of the mobile robot which accomplish using low-cost open-source hardware such as Arduino and Raspberry Pi. The robot is connected wirelessly via a low-power ZigBee module to the control station to allow the operator for controlling the mobile robot motions and monitoring the physical events in the environment where the robot is used. Sensors such as camera, temperature, and range are embedded in the robot to sense and monitor human motion, the room temperature, and the distance of the surrounding obstacles. The testing of the implemented mobile robot shows that it can run continuously for approximately 6.5 hours at a motor shaft speed 25 rpm of unlit the need to recharge the battery.